Comparing foreign accent in L1 attrition and L2 acquisition: Range and rater effects. (July 2014) - Schmid, Monika S.; Hopp, Holger
This study examines the methodology of global foreign accent ratings in studies on L2 speech production. In three experiments, we test how variation in raters, range within speech samples, as well as instructions and procedures affects ratings of accent in predominantly monolingual speakers of German, non-native speakers of German, as well as long-term emigrants from Germany, that is, L1 attriters. The findings show that rater differences do not result in systematic changes in rating patterns. In contrast, range effects and effects of familiarity with accented speech lead to shifts in absolute and relative ratings. Including more strongly foreign-accented samples leads to lower judgements for the entire group of L2 speakers compared to natives. Similarly, lower familiarity with foreign accent results in more variable and more strongly foreign-accented judgements. We discuss the implications for research on L2 pronunciation as well as for the interpretation of nativeness in L2 studies and language testing more generally.